2017
DOI: 10.1038/aps.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a self-adjuvanted iTEP-delivered CTL vaccine

Abstract: Cytotoxic T lymphocyte (CTL) epitope peptide-based vaccines are widely used in cancer and infectious disease therapy. We previously generated an immune-tolerant elastin-like polypeptides (iTEPs)-based carrier to deliver a peptide CTL vaccine and enhance the efficiency of the vaccine. To further optimize the vaccine carrier, we intended to potentiate its function by designing an iTEP-based carrier that was able to deliver adjuvant and a vaccine epitope as one molecule. Thus, we fused a 9-mer H, a peptide derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…These findings are consistent with previous studies indicating that the free HMGB-1-derived peptide has almost no effect on the maturation and activation of DCs [31]. They are also consistent with results of studies showing that the adjuvant covalently linked to the short peptides could stimulate higher epitope recognition than the physically mixed formulation of the same molecules [39,40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with previous studies indicating that the free HMGB-1-derived peptide has almost no effect on the maturation and activation of DCs [31]. They are also consistent with results of studies showing that the adjuvant covalently linked to the short peptides could stimulate higher epitope recognition than the physically mixed formulation of the same molecules [39,40].…”
Section: Discussionsupporting
confidence: 93%
“…As mentioned previously, the success of peptide-based vaccines mainly depends on the utilized peptides and selection of an appropriate adjuvant. Herein, it has been found that the covalent linking of adjuvant to tumor-associated antigens (TAAs) could result in the maturation and activation of DCs in vitro and induced a potent antitumor immune response in vivo compared to TAAs which they physically mixed with adjuvant [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The linker was also inserted in between the ABD domain and the PE domain of ABD-PE. The coding genes of αPD-1-ABD-PE and αPD-1-PE were generated by fusing the synthesized genes together using a previously described protocol 52,53 . Meanwhile, a gene that encodes the linker was inserted between the genes of αPD-1…”
Section: Generation Of Expression Vectors For Recombinant Proteinsmentioning
confidence: 99%
“…42,43 To evaluate the risk of autoimmunity induction by overexpressed self-antigen-derived peptide vaccinations, several preclinical and clinical trials have demonstrated that peptides derived from overexpressed self-antigens were able to induce effective and specific CTL responses without any serious systemic adverse events. [44][45][46][47] However, studies by Overwijk and Restifo 48 and Overwijk et al 49 revealed that potent CD8 + T-cell responses induced with MDA in melanoma patients could interact with melanocytes in the skin, resulting in autoimmune depigmentation. Therefore, if hPEBP4-derived peptides are to serve as candidates for CTL-based immunotherapy against breast cancer or other hPEBP4-expressing carcinomas, their safety and tolerability need to be further assessed in basic and clinical studies.…”
Section: Discussionmentioning
confidence: 99%